Testing the alkenone D/H ratio as a paleo indicator of sea surface salinity in a coastal ocean margin (Mozambique Channel). (January 2015) - Kasper, Sebastian; van der Meer, Marcel T.J.; Castañeda, Isla S.; Tjallingii, Rik; Brummer, Geert-Jan A.; Sinninghe Damsté, Jaap S.; Schouten, Stefan
Highlights: A 39 ka record of δDalkenone reflected hydrological change in the Mozambique Channel. No clear glacial – interglacial shift was observed in δDalkenone . Glacial alkenones were depleted in D due to low sea level and freshwater discharge. Low sea level/high freshwater input during glacial was reflected in high BIT index. Positive correlation of glacial BIT/δDalkenone suggests coastal haptophyte input. Abstract: Reconstructing past ocean salinity is important for assessing paleoceanographic change and therefore past climatic dynamics. Commonly, sea water salinity reconstruction is based on planktonic foraminifera oxygen isotope values combined with sea surface temperature reconstruction. However, the approach relies on multiple proxies, resulting in rather large uncertainty and, consequently, relatively low accuracy of salinity estimates. An alternative tool for past ocean salinity reconstruction is the hydrogen isotope composition of long chain (C37 ) alkenones (δDalkenone ). Here, we have applied δDalkenone to a 39 ka sedimentary record from the Eastern South African continental shelf in the Mozambique Channel, close to the Zambezi River mouth. Despite changes in global seawater δD related to glacial – interglacial ice volume effects, no clear changes were observed in the δDalkenone record throughout the entire 39 ka. The BIT index record from the same core, which provides information on relative contributions of soil organic matter (OM) vs. marine input, indicates high soil OM input during the glacial and low input during the Holocene. This suggests a more pronounced freshwater influence at the core location during the glacial, resulting in alkenones depleted in D during that time, thereby explaining the lack of a clear glacial-interglacial alkenone δD shift. The correlation between the BIT index and δDalkenone during the glacial period suggests that increased continental runoff potentially changed the growth conditions of the alkenone-producing haptophytes, promoting coastal haptophyte species with generally more enriched δDalkenone values. We therefore suggest that the application of δDalkenone for reconstructing past salinity in coastal settings may be complicated by changes in the alkenone-producing haptophyte community.